2015
DOI: 10.5688/ajpe79338
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Residents’ Pursuit of Academic Positions

Abstract: Objective. To describe pharmacy residents' interest in and pursuit of academic positions.Methods. An electronic presurvey and postsurvey were sent to pharmacy residents during the 2011-2012 residency year. The initial survey evaluated residents' job preferences and interest in academia at the beginning of residency, and the follow-up survey focused on job selection and reasons for pursuing or not pursuing positions in academia.Results. Nine hundred thirty-six residents responded to the initial survey and 630 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…While providing such fundamental training is not required by the ASHP accreditation standards or the ASHP CAGO for PGY1 pharmacy residency programs, the ACCP Educational Affairs Committee guidelines recommendations on pharmacy resident teaching experiences makes this responsibility one of the goals and outcomes for residents achieving a quality teaching experience . One study noted that 23% of the residents who did not apply for a faculty position did so because of lack of adequate preparation to teach and that residents who complete teaching programs are more likely to apply for and accept faculty positions, highlighting the importance of this fundamental knowledge that is needed to prepare residents for teaching experiences . Therefore, it is imperative that all ASHP‐accredited PGY1 pharmacy residency programs make this fundamental training activity a requirement for basic teaching experiences for residents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While providing such fundamental training is not required by the ASHP accreditation standards or the ASHP CAGO for PGY1 pharmacy residency programs, the ACCP Educational Affairs Committee guidelines recommendations on pharmacy resident teaching experiences makes this responsibility one of the goals and outcomes for residents achieving a quality teaching experience . One study noted that 23% of the residents who did not apply for a faculty position did so because of lack of adequate preparation to teach and that residents who complete teaching programs are more likely to apply for and accept faculty positions, highlighting the importance of this fundamental knowledge that is needed to prepare residents for teaching experiences . Therefore, it is imperative that all ASHP‐accredited PGY1 pharmacy residency programs make this fundamental training activity a requirement for basic teaching experiences for residents.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 One study noted that 23% of the residents who did not apply for a faculty position did so because of lack of adequate preparation to teach and that residents who complete teaching programs are more likely to apply for and accept faculty positions, highlighting the importance of this fundamental knowledge that is needed to prepare residents for teaching experiences. 5 Therefore, it is imperative that all ASHP-accredited PGY1 pharmacy residency programs make…”
Section: Fundamental Knowledge In Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Shin et al found that over 60% of PGY2s reported interest in academia at the beginning of their residency with 24% securing a faculty position by the end of their residency. 42 Residents who completed a TLC program were more likely to apply for and accept a position within pharmacy education. In addition, several studies have reported the positive perceived utility of TLC programs from the perspective of program participants.…”
Section: Discussionmentioning
confidence: 99%